Clinical InvestigationsOriginal articleThe rectum and bladder doses in intracavitary brachytherapy for cervical cancer - Sharma, Brahmacharimayum Arunkumar; Singh, Tomcha (Journal of Contemporary Brachytherapy, 2010)
Purpose : The aim of this work was to study the International Commission on Radiation Unit and Measurement (ICRU) for rectum (rICRU) and bladder (bICRU) dose behaviors in the treatment of cervical cancer by high dose rate (HDR) intracavitary brachytherapy (ICRT). Material and methods : A retrospective study was carried out on 38 patients with a total of 38 fractions (1st fraction of each patient) of cervical cancer treated with HDR intracavitary brachytherapy in addition to external radiotherapy (EBRT). Manchester system using standard source loading pattern were used in the planning. Normal distributions were tested to the rICUR and bICRU doses for any statistical conclusions. Results : It was observed that rICUR and bICRU of the population under study is found to show normal distribution at 5% level of probability with mean dose of 65% and 61% and standard deviation of 15% and 21%, respectively. Conclusions : The normality behavior of the rectal and bladder doses suggests that not less than 80% of population (patients) receive rectal and bladder doses less than 80% of the prescribed dose at point A.